The Mitigation of Threats and Risks in the Process of Virtualization by Securing the Hypervisor Control Factor - A. S. Thiabp,; A. S. Shibghatullah, (Journal of Advanced Research in Computing and Applications, 2023)
A study was undertaken in order to be able to understand the threats and the risks to the hypervisor’s control of the virtual machines on the virtual platform. The study undertaken has clearly shown that even though a probability exists, the level of trust of clients and service providers helps to reduce the levels of risks and threats to the virtualized platform. A test bed was created and a network of (un) modified hosts were subjected to security disruptions and intrusions. The hypervisor has been used so that it can be observed and recreated. The test bed used the hypervisor as an instrument to gather the information. The information gathered across was an entire heterogeneous LAN that was generalized for the experiment. This helped in the observation process and control of the behavior of the virtual machines. The main security events were logged which was a new process that the hypervisor was enabled with for the experiment. It showed that the hypervisor can intercept a system call before it is allowed to enter.